Between Canvassing and Clicks: Analyzing the Impact of Digital Transformation on SME Growth - Satria Hari Pratomo; Vanessa Vanessa (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
This study investigates the effectiveness of digital transformation in enhancing client acquisition, using a case study of a lamp business in Indonesia. Established in 2021, the company initially operated through traditional offline channels but expanded to online platforms in 2022, integrating digital tools including AI-based financial management systems to streamline operations and support decision-making. The research focuses on comparing offline and online strategies, examining key performance indicators such as revenue contribution, customer acquisition costs, conversion rates, and operational challenges encountered in both modes. In addition, the study explores whether the observed revenue growth following digitalization is primarily driven by online sales or whether it benefits from a hybrid approach that combines both online and offline channels. By analyzing these aspects, the study seeks to provide insights into the practical implications of digital transformation for small and medium-sized enterprises (SMEs), particularly in the Indonesian market. The findings are expected to clarify whether adopting digital strategies offers a measurable advantage over traditional methods in terms of efficiency, cost-effectiveness, and market reach. Ultimately, this research aims to inform SME owners and managers about best practices for leveraging digital tools to enhance client acquisition and drive sustainable business growth.